FRI0283 Clinical course of mesangial lupus nephritis in a cohort of argentinian patients. (23rd January 2014) - Collado, M.; Gomez, G.; Gargiulo, M.; Colaianni, I.; Suarez, L.; Dorado, E.; Zazzetti, F.; Chaparro del moral, R.; Martinez, A.; Ortiz, A.; Galván, I.; Juarez, V.; et al.
Abstract : Background: Mesangial lupus nephritis (MLN) is thought to follow a benign course although there are studies that show otherwise(1, 2 ). Objectives: Our aim was to describe the clinical progression in patients with MLN. Methods: retrospective, multicentric study in patients with systemic lupus erythematosus and MLN (ISN/RPS 2003) on the first renal biopsy and at least 12 months of post-biopsy follow-up. Demographic, clinical and laboratory characteristics were reviewed. Treatment response was rated based on the EULAR/ ACR criteria(3 ). Patients were divided into two groups: responders (R)[complete (CR) and partial (PR)] and non-responders(NR):[NR, chronic renal failure(CRF), histology transformation(HT)]. Favorable long term outcome was considered if the patient remained at CR or PR at the last evaluation. Unfavorable was defined as transformation to a proliferative or a membranous type or CRF at any time. The Mann-Whitney test was used to compare numerical variables, Fisher's exact test to compare ratios. Results: Twenty-seven patients (23 females) were assessed. Mean age at the time of first biopsy: 28.2±9 years old. Median time from SLE diagnosis to first biopsy: 1 year (range=0-6). Median time from onset of signs of nephropathy and first biopsy: 2 months (range=0-15). The presentations were: proteinuria > 0.5g/24hr: 19 patients (7 nephrotic-range), 13 hematuria, and 1 impaired renal function requiring dialysis. After the first biopsy 27 patients received corticosteroid therapy (0.5-1mg/kg/day) and 7 received another immunosuppressant for non-renal reasons. At 12 months of follow-up, 20 R(10 RC, 10 PR) and 6 NR (4 NR, 1CRF, 1HT). We had a missing data. The demographic data and immunology laboratory were similar between R and NR. Responders had a significantly lower level of 24-hour urine protein excretion(g/24hs) at 6 (0, 06 vs 0, 8)p=0, 03 and 12 months (0, 2 vs 3, 2) p=0.03. Creatinine levels not differ between groups. In the R group 65% of patients received hydroxychloroquine and 15% immunosuppressant vs 100% and 50% respectively in NR group. At the five year follow-up 21 patients were evaluated (6 not reach 5 years of follow up);11 had been re-biopsied: renal flare 8, NR 3. Median time between 1st and 2nd biopsy: 25 months (11-52). Histology results: 1 Class II, 2 Class III, 5 Class IV, 3 Class V. Ten patients continued in remission at 5 years (7 CR, 3PR) and 11were NR (10 HT, 1CRF). The outcome remained favourable in 10/21(47, 6%) and unfavourable 11/21(52, 3%) patients, including 10 patients who transformed and one with CRF. There were no deaths. Conclusions: Our group of patients had a high rate of progression to more serious classes of nephritis (47.6%) after five years of follow up. A higher degree of proteinuria was the only data that shown correlation with histology progression. Serologic markers of lupus activity were not different among R and NR group. References: References Lupus(2003)12:665-671, RheumatolInt(2012)32:2459-2464, Lupus(2009)18, 257-263. Disclosure of Interest : None Declared